ANALISA KANDUNGAN TIMBAL PADA TERASI SERTA GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP PEDAGANG TENTANG BAHAYA TIMBAL DI PASAR TRADISIONALKOTA MEDAN TAHUN 2018 - Marlinang Isabella Silalahi (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2018)
Terasi is a preserved product of small fish or rebon which is processed through a process of fermentation, milling, and drying lasting Â± 20 days. In the shrimp paste product, salt is added to function as a preservative, in the form of a paste, black and brown, and added to the dye to be a reddish color. In the city of Medan in 2013 found shrimp paste containing lead, Ihsan Fahri Angkat's research in the Seikambing market found that unbranded shrimp paste containing lead amounted to 1.88mg / kg (ppm) and found in the Aksara Market branded shrimp paste containing lead of 1.80mg / kg ( ppm) which passes the BPOM (Drug and Food Inspection Agency) threshold value of 1.0mg / kg (ppm). The purpose of the study was to determine the analysis of lead content in shrimp paste as well as an overview of the level of knowledge and attitudes of traders about the dangers of lead in traditional markets. This research is a descriptive research. The research subjects were all traders selling shrimp paste in the Medan Market Center, Petisah Market and Seikambing Market and the object of this research was branded and unbranded shrimp paste which was sold at the Medan Market Center, Petisah Market and the Seikambing Market. Data was collected through interviews using questionnaires in the subject group and on objects obtained from laboratory results. The object data obtained was analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that there was a lead content in shrimp paste ranging from 0.130-0.484 mg / kg. For an overview of the level of knowledge of traders on shrimp paste has good knowledge as many as 18 people (60%) and less knowledge as much as 2 people (6.7%) and the description of the attitude of traders to shrimp paste has a good attitude of 24 people (80.0%) and moderate attitude as many as 6 people (20.8%). It is hoped that traders and the public will increase their insight into the lead content in shrimp paste circulating in the community so they prefer to choose a good paste to consume and to know the harmful effects if lead is in the human body.